PENGEMBANGAN PERANGKAT PEMBELAJARAN MENGGUNAKAN MODEL SIKLUS BELAJAR 5E PADA MATERI KOLOID DALAM MENINGKATKAN PEMAHAMAN KONSEP SISWA - Sartika, Rody Putra (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2014)
This study aims to describe students' understanding of concepts using learning cycle 5E model in the topic of colloid. This type of research is developmental research used Dick and Carey model on treatment by using the One Group Pre-test and Post-test design. Data collection methods used were observationand tests, while the data analysis techniques used qualitative descriptive analysis and Wilcoxon matched pairs test (α = 5%). The results of this research are learning materials of lesson what have been developed had a validity, generally very good category to be used. Implementation of application of learning materials developed is very good, improving students’ learning outcomes which we can see from the completeness of individually and classically, as well as enhancing students' understanding of concepts revealed by normalized gain score with high category.